Epigenetics and Physical Exercise: Modulation of Gene Expression in Individuals with Hereditary Predisposition to Dyslipidemia (CIPEEX, 2026)
Introduction: Dyslipidemia is a major risk factor for cardiovascular disease, influenced by both genetic and epigenetic determinants. Modifiable factors, such as diet and physical exercise, can mitigate complications even in genetically predisposed individuals. Exercise, whether performed alone or in combination with statins, contributes to the regulation of lipid profiles and cardiometabolic parameters, while also exerting potential epigenetic effects. Methods: A literature search was conducted in the PubMed, SciELO, and LILACS databases (2014–2024) using the descriptors exercise, dyslipidemia, and epigenetics. A total of 46 articles were retrieved; after duplicate removal, 34 were screened by title and 12 by abstract. Eight studies met the inclusion criteria, including experimental, randomized, and longitudinal trials. Results: Moderate-intensity exercise was associated with reductions in triglycerides, LDL cholesterol, and epicardial fat, as well as improvements in maximal oxygen uptake and insulin resistance. Interventions combining diet, exercise, and statins further enhanced these outcomes. Studies involving aquatic exercise and interventions during pregnancy also demonstrated additional benefits, including intergenerational effects. Conclusion: Physical exercise is an effective intervention for managing dyslipidemia and reducing cardiovascular risk, with the potential to modulate gene expression related to lipid metabolism.
Keywords: Physical Exercise; Dyslipidemia; Epigenetics